Regioselective and stereoselective sulfonylation of alkynylcarbonyl compounds in water. Issue 18 (9th August 2016) - Li, Wenyi; Yin, Guoxing; Huang, Lei; Xiao, Yan; Fu, Zhimin; Xin, Xiu; Liu, Fang; Li, Zhizhang; He, Weimin
Abstract : A simple and efficient route for the synthesis of Z -β-sulfonyl-α, β-unsaturated carbonyl compounds by using water as the solvent and hydrogen source is developed. Abstract : With water as the reaction medium, an efficient protocol has been developed for the synthesis of Z -β-sulfonyl-α, β-unsaturated carbonyl products via water-promoted sulfonylation of alkynylcarbonyl compounds with sodium sulfinates. This strategy could effectively avoid the use of toxic organic solvents, catalysts and additives. This method features a wide substrate scope with a broad range of functional group tolerance, utilizes easily available starting materials, can be scaled-up, and is operationally simple.